Experimental study on the mechanical and durability properties of concrete with waste glass powder and ground granulated blast furnace slag as supplementary cementitious materials. (15th December 2017) - Ramakrishnan, K.; Pugazhmani, G.; Sripragadeesh, R.; Muthu, D.; Venkatasubramanian, C.
Highlights: Synergic effect of waste glass power (GP) with ground granulated blast furnace slag (GGBS) was studied. The percentage of cement content in concrete was kept constant at 50%. Different combined proportion of GP and GGBS was used to replace the remaining 50% of cement. GG77 mix (50% cement + 15% GP + 35% GGBS) was found to possess good mechanical and durability properties. Abstract: This paper presents a laboratory study on the influence of combination of crushed waste glass powder (GP) and ground granulated blast furnace slag (GGBS) as a partial replacement in cement, on the behaviour of mechanical and durability properties of concrete. The mechanical properties were examined by the tests of compressive strength, flexural strength, bond strength and split tensile strength. Durability aspects viz., water absorption and sorptivity were examined. Replacement of cement by GP was from 5% to 45% in step of 5% and the GGBS with range of replacement from 45% to 5% in step of 5% respectively. In total, ten different combinations of mixes were studied at three different ages of concrete namely 3, 7 and 28 days of concrete. The optimum mix was selected from the 3, 7, 28-days age compressive strengths of different mixes. The combined mix (cement + GP + GGBS) as 50:15:35 and 50:20:30 increased the compressive strength by 44.20% and 43.08% respectively. Similarly the split tensile strength of the combined mix (cement + GP + GGBS) with 50:15:35 and 50:20:30 increased the split tensile strength value over the control mix by 9% and 7.6% respectively. It was found that addition of GP and GGBS reduced the sorptivity rate and water absorption rate. This study also shown that GP and GGBS can be successfully utilized as an effective mineral admixture in cement concrete with 15% and 35% respectively as a optimal replacement of cement in combined manner.